Language Teaching and Activity Efficiency for Primary School Students - qizi, Eshaliyeva Ozoda Abdurahmon (European Journal of Life Safety and Stability (2660-9630), 2022)
This article reveals the methodological features of teaching English vocabulary as the main didactic activity when working with children. Challenging yet pleasurable communicative approach promotes positive attitude toward the daily study in language learning. Pupils working in groups have comprehension activity, journal sharing, question discussion and role-playing of the characters in the books or plays. Communicative approach not only lightens classroom anxiety but also promotes pupils cooperative learning and enhances their communication abilities.